A procedure for minimization of nosocomial infections risk through upgrading and re-architecting of healthcare facilities - Parsia, Yasaman (2019)
As manager of each organization such as healthcare facilities (HFs), it is his/her responsibility to maintain a safe and healthy workplace against various risks. Nosocomial infections (NIs), also known as HF cross-infections is one of these risks in HFs. These infections can increase the rate of mortality, morbidity, emotional stress, and prolong hospitalization for patients and also creates additional cost for both patients and HFs across the world, especially in Kerman/Iran as a case of this study. Departments of HFs have a significant effect on transmission of NIs from one patient to other patients and from one department to the other ones. Departments can be source of infections in HFs and it seems so important to find risky departments in controlling NIs. It can be a good decision for HFs managers to find risky and low risky departments to remove or rearchitecting/add or upgrading in HF, respectively, to control NIs. Based on literature review there isn’t study, if any, by considering this note to control NIs and managers still need more effective models for infection control in healthcare facilities through layout modification decisions. Most of the researchers just try to reduce the risk of this infection through medical study such as introduce new antibiotics or through architecting research by attention to layout design elements for example, type of equipment or through management by preparing some electronical systems to control personnel in fields of personal hygiene. Recognition the risky and/or low risky departments during upgrading and/or re-architecting of HFs can help the managers to reduce the rate of NIs in their HF. Otherwise, less attention to this note during upgrading and re-architecting of HFs can be a factor to increase the risk of NIs. Therefore, the first and second objectives of the current study were to propose a systematic decision-making (DM) procedures with a mathematical approach as a new solution for NI control in HF through upgrading and/or re-architecting DM. It is argued that hybridization of the methods can integrate their results for final DM and create an opportunity of integrating criteria importance into the value of utility function. Thus, Weighted Sum Method (WSM), Decision-making Trial and Evaluation Laboratory (DEMATEL), and Expanded DEMATEL, together with the modified Nominal Group Technique (NGT) for decision data-collection, were adopted for the development of the procedures. Selection of the MADM methods was based on benchmarks, such as their analysis capability, ease-of-use and etcetera. To achieve objective one, WSM with Expanded DEMATEL and for objective two DEMATEL with WSM are defined. An expert consulted to comment validity of the proposed procedures. As third objective, the feasibility test of the proposed procedures, a case study was accomplished. A large size hospital in Kerman/Iran with 400 beds and 20 departments was selected for the case study. The results of the proposed procedures calculated based on the collected data from the case. Lastly, validity and feasibility of the proposed procedures obtained by confirming the results by top management of the case. To conclude the finding of this research, considering the issue of NIs for patients and HFs, the presented decision-making procedures for upgrading and re-architecting of HFs, practically, could contribute to the minimization of NIs risk. They are, theatrically, are novel decision-making procedures for HF managers which can be a considerable solution to overcome challenges of multiple-criteria layout-modification decisions align with controlling the NIs. Last but not least, as a social contribution, the procedures of this study will be an asset for public health.